Incidence of Tuberculosis in Inflammatory Rheumatic Diseases: Results from a Lithuanian Retrospective Cohort Study - Miltinienė, Dalia; Deresevičienė, Giedrė; Nakčerienė, Birutė; Davidavičienė, Valerija Edita; Danila, Edvardas; Butrimienė, Irena; Dadonienė, Jolanta (Medicina (Kaunas, Lithuania), 2020)
Background and objective: With an increase in survival rates among rheumatic patients, comorbidities and infections, in particular, have gained more importance, especially after the introduction of biologicals to the treatment algorithms. Tuberculosis (TB) infection has always been given a special attention in patients with rheumatic diseases (RD). Although Lithuanian population has one of the highest TB incidence rates among European countries, the incidence of TB in the rheumatic patients’ population is still unknown. The aim of this study was to assess the incidence rate of TB in an inflammatory RD retrospective cohort and to compare that rate with a rate in a general population. Material and Methods: Patients with the first-time diagnosis of inflammatory RD during the period between 1 January 2012 and 31 December 2017 were identified from the Lithuanian Compulsory Health Insurance Information System database SVEIDRA. All cases were cross-checked with Health Information center at the Institute of Hygiene, for the vital status of these patients and date of death if the fact of death was documented, and with Tuberculosis Register operated by Vilnius University Hospital Santaros Klinikos, for the confirmation of TB cases. Sex and age standardized incidence ratios (SIR) were calculated by dividing the observed numbers of TB among rheumatic patients by the expected number of cases, calculated using national rates from Lithuanian Department of Statistics Official Statistics website. Results: Overall, 8779 patients with newly diagnosed RD were identified during the 2013–2017 period, these included 458 patients who used biological disease modifying drugs (bDMARDs). The mean duration of the follow-up period was 2.71 years. The cohort consisted mainly of women (70%) and a half of the cohort were rheumatoid arthritis (RA) patients (53%). Mean age of patients at the time of RD diagnosis was 56 years (range = 18–97 years). There were 9 TB cases identified during 23,800 person years of follow-up: 2 cases among them were treated with bDMARDs. The mean calculated annual TB incidence in RD cohort was 37.81 per 100,000 person years, which is consistent with the incidence rate predicted by national estimates, with a resultant SIR of 0.90 (0.41–1.70). The unadjusted hazard ratio for bDMARD use versus no bDMARD use was 4.54 (0.94; 21.87) in a total cohort and very similar in rheumatoid arthritis cohort; in both cohorts, it was not a statistically significant risk. Conclusions: Here, we present the first nationwide cohort study to assess the incidence of TB in a broad spectrum of inflammatory RD. Although limited by short follow-up period, this study shows that TB incidence in RD cohort does not exceed TB incidence in the general Lithuanian population.